Abnormal thermal conduction and stochastic resonance phenomenon in a finite lattice system - Yiran Li; Jiaquan Wu; Fei Ye; Xinyu Zhang (AIP Advances, 2023)
This paper studies the thermal conduction of Frenkel–Kontorva (FK)-ϕ4 lattices with the finite number of atoms under a periodic force. Through numerical simulations, we find that in the thermal conduction of non-linear lattices, external periodic signals can act in conjunction with noise to create stochastic resonance behaviors and that some adjustable dynamical parameters, such as the onsite potential of the FK and ϕ4 lattices, the amplitude and frequency of external periodic signals, can regulate heat flux. Our study results can provide a sufficient theoretical basis for the fabrication of thermal devices and the control and utilization of thermal energy.